Correlating mutated ampC gene expression with ampc beta-lactamase hydrolysis activity in stenotrophomonas maltophilia - Shit, Chong Seng (2014)
As a member of β-lactamase producing bacteria, Stenotrophomonas maltophilia gains attention because of its multiple drug resistance characteristic. L1 and L2 β-lactamases are the dominant β-lactamases produced by S. maltophilia. However, the production of other obscure β-lactamases by S. maltophilia has been reported as well. As a result,domination of β-lactam resistance by L1 and L2 β-lactamases is no longer valid. Thus,it is possible for S. maltophilia to produce AmpC β-lactamase. AmpC β-lactamase synthesized by ampC gene of S. maltophilia is predicted to have hydrolytic activity as published in the National Center for Biotechnology Information (NCBI) database. In addition, the presence of SXSK and YXN elements in the predicted amino acid sequence represented features of AmpC β-lactamase. This enzyme could confer resistance to cefepime (4th generation cephalosporins) and other cephalosporins groups. Since little is known about the function of ampC gene, characterization of ampC gene profile in S. maltophilia is crucial. A total of 78 isolates of S. maltophilia were collected from Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Kuala Lumpur in year 2009. Most of the isolates were collected from ICU patients (62.1%) and the most frequent isolation site was from blood sample (39.4%). Great genetic diversity was determined among the clinical isolates by pulsed-field gel electrophoresis (PFGE). Only four antibiotics exhibited effectiveness against S. maltophilia infection which is co-trimoxazole (100% susceptibility), polymyxin-B (100% susceptibility), ciprofloxacin (98% susceptibility),and cefepime (98% susceptibility). A cefepime- and ceftazidime-resistant S. maltophilia strain was isolated with MIC values of ceftazidime (64 mg/L) and cefepime (48 mg/L). Thus, screening of ampC gene by Polymerase Chain Reaction (PCR) was performed since most of the cefepime resistance issue found in other bacteria such as Escherichia coli, Acinetobacter baumannii, and Enterobacteriacaea are related to overexpressed and/or mutated ampC gene. The presence of ampC gene was determined in most of the clinical isolates (68 out of 78 isolates, 87%) including S. maltophilia ATCC 13637. Nucleotides alignment showed ten nucleotides differences between cefepime-resistant isolate (CX isolate) and cefepime-sensitive S. maltophilia ATCC 13637. These mutations have resulted in four amino acids sequence changes. Noticeably, two identical mutation points were found in the predicted ampC amino acid of S. maltophilia k279a (published in NCBI database) and clinical S. maltophilia CX isolate compared to S. maltophilia ATCC 13637. Furthermore, SXSK and YXN elements which represented features of AmpC β-lactamase also were found in the amino acid sequences. Characterization of ampC gene was carried out in order to figure out the function of the gene and its expressed protein. Gene characterization by cloning could prevent the overlapping function of L1 and L2 β-lactamase genes with the ampC gene. The expressed protein from ampC gene of CX isolate showed greater hydrolytic activity towards tested substrates compared to the expressed protein from ampC gene of S.maltophilia ATCC 13637 isolate. The first β-lactam ring antibiotic, penicillin; the second to the fourth generation of cephalosporins, cefoxitin, ceftazidime, and cefepime were chosen as substrates for kinetic assay. Lastly, the expression level of ampC gene of clinical CX isolate and cefepime-sensitive S. maltophilia ATCC 13637 was compared. Relative quantitative real-time reverse transcriptase polymerase chain reaction (qPCR) assay was designed for gene expression study. Relative quantification qPCR showed a significant higher expression level of ampC gene in the clinical CX isolate compared to S. maltophilia ATCC 13637. In addition, L1 and L2 β-lactamase genes in clinical CX isolate and S. maltophilia ATCC 13637 were expressed at the same level. In conclusion, this study demonstrated that although most of the clinical S. maltophilia isolates including S. maltophilia ATCC 13637 carry ampC gene, only mutated ampC gene resulting in changes of amino acids sequence does lead to cefepime resistance. Remarkable findings in this study especially the identical mutation points found in both clinical CX isolate and the S. maltophilia k279a could be an interesting exploration in future.